2009
DOI: 10.1111/j.1872-034x.2008.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasonographic evaluation of hemodynamics related to variceal relapse in esophageal variceal patients

Abstract: Endoscopic ultrasonographic evaluation of the hemodynamics in esophageal varices before and after EIS enables prediction of early variceal recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 19 publications
0
28
1
Order By: Relevance
“…Residual veins in the esophagus wall have been reported to be associated with a high risk of the reoccurrence of varices. [5] Based on this, we recommend EUS after EVL; however, the patient in the present case refused. In consideration of the high risk of recurrence, he underwent endoscopy 6 months later, and the recurrence of esophageal varices was observed.…”
Section: Discussionmentioning
confidence: 88%
“…Residual veins in the esophagus wall have been reported to be associated with a high risk of the reoccurrence of varices. [5] Based on this, we recommend EUS after EVL; however, the patient in the present case refused. In consideration of the high risk of recurrence, he underwent endoscopy 6 months later, and the recurrence of esophageal varices was observed.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, identification of patients with large “deep” varices is of clinical importance. Also, an advanced hemodynamic study utilizing endoscopic color Doppler ultrasonography showed its potential usefulness in predicting recurrent variceal bleeding [17]. …”
Section: Discussionmentioning
confidence: 99%
“…The size of such peri-esophageal veins appears to correlate with bleeding risk [2]. Several studies have also confirmed that the ongoing presence of these veins after endoscopic treatment is associated with an increased risk of recurrence [3,4]. …”
Section: Esophageal Varicesmentioning
confidence: 99%